A device for performing whole bone torsional testing in a single-axis linear motion testing machine - Tyler, J. M.; Larinde, W.; Elder, S. H. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
Objectives: To design a device for the conversion of linear to rotational motion and to use it in order to determine torsional properties of canine tibiae in a universal tension/compression testing machine. Methods: A fixture incorporating a cable and pulley at one end and a guide block and rail assembly at the other was used to test 10 whole canine tibiae to failure in torsion at 1°/s. Results: The device produced spiral fractures in all tibiae. Torsional strength and stiffness were 13.9 ± 1.4 N m and 0.53 ± 0.07 N m/degree, respectively. Clinical significance: This inexpensive device can be used to evaluate the mechanical properties of long bones after various interventions to improve fracture healing. The device can be adapted for use with any single-axis linear motion testing machine. Assessment of fracture healing often includes loading to failure in torsion (1–5). Torsional testing is typically performed using a biaxial servohydraulic testing machine or similar sophisticated electromechanical equipment. Due to its high cost, many researchers do not have such equipment at their disposal. However, uniaxial tension-compression testing machines are widely available. Therefore, a device that can be used to perform torsional testing in a tension-compression machine would be beneficial. In this study we present a custom fixture for converting the vertical linear motion of a universal testing machine to rotational motion and validate its performance in torsional testing of canine tibiae.
Keywords: Torsion; testing fixture; whole bone biomechanics